Aseptic preparation hands-on workshop: Mastering the fundamentals of aseptic techniques / Nik Aisyah Najwa Nik Mustaffa Shapri and Associate Prof. Dr. Mahmathi Karuppannan - Nik Mustaffa Shapri, Nik Aisyah Najwa (Faculty of Pharmacy, 2023)
On 4th September 2023, the Department of Clinical Pharmacy organised a hands-on workshop on aseptic preparation with eleven laboratory staff and lecturers. The workshop was held at Hospital Al-Sultan Abdullah (HASA) and led by two experienced HASA aseptic unit pharmacists, Ms. Akmal Afifah Alias and Ms. Amira Nadzira Abdul Hamid. The workshop aimed to enhance the aseptic skills and knowledge of lecturers and lab staff, particularly the teaching staff of PHC671 (Applied Therapeutics in Infectious Disease and Neoplastic Disorder) course, where students receive in-house aseptic preparation training. This workshop includes explanations and hands-on training by the experienced pharmacists.